Effects of the FIFA World Cup Qatar 2022 on match running performance in the Spanish professional soccer league: A pilot study - García-Calvo, Tomás; Ponce-Bordón, José Carlos; Lobo-Triviño, David; López del Campo, Roberto; Resta, Ricardo; Raya-González, Javier (Biology of Sport, 2025)
The FIFA World Cup Qatar 2022 was scheduled during the in-season period of the European teams, impacting soccer clubs’ routines. This study aimed to analyse the influence of the FIFA World Cup Qatar 2022 on match running performance in the First Spanish soccer league, considering the players’ participation. A total of 11,530 individual match observations from 582 professional soccer players competing in the First Spanish soccer league ( n = 370 matches) over the 2022/23 season were collected. Soccer players were classified according to participation in the World Cup: participants and non-participants. Pre-World Cup (1 st –14 th match day) and post-World Cup (15 th –38 th match day) periods were compared. Match running performance was obtained by the Mediacoach video tracking system in accordance with LaLiga. During the pre-World Cup period, no significant differences between groups were found, while in the post-World Cup period, non-participants covered significantly greater total distance, and distances at low, medium, and high speeds compared to the counterparts. No significant differences were observed between the periods for participants, although non participant players covered a greater total distance, and distances at low, medium, high, and very high speeds, and sprinting during the post-World Cup period compared to the prior period. These results favour the inclusion of a long winter break in LaLiga to maintain or improve the physical performance of soccer players. Additionally, specific periodization of workload and recovery strategies for players participating in an international championship during the in-season period are crucial to prevent a decline of subsequent performance